THE EFFECTS OF ONLINE LEARNING ON PG-PAUD STUDENTS’ ENGLISH LEARNING ACHIEVEMENT ASSESSED FROM THEIR PRIOR KNOWLEDGE IN THE EVEN SEMESTER OF 2019/2020 ACADEMIC YEAR - Hendra Husnussalam (IKIP Siliwangi, 2021)
In the midst of the current outbreak of the Covid-19 virus, online learning, including learning English, is the right choice. This type of learning in its implementation requires supporting applications. Among the applications that can be used for learning English include Zoom, and Google Classroom. The use of these applications will be examined through this research. The use of this application aims to see the increase of ability in learning English course, namely in terms of reading skill. The participants in question are 12 2018 students majoring in Early Childhood Education (PG-PAUD) who, in the even semester of the 2019/2020 Academic Year, took the course English for Scientific Works, so at the same time, they are the samples of this research. The method used in this research is descriptive qualitative and the design is a case study. The results show that the participants can improve their English skills, especially in reading and writing, through this online learning. The proof is that their scores, both in every meeting and mid-term or last-term test, have always improved. Keywords: Online Learning, Learning Achievement, English